Revision of the genus Minagrion Santos, 1965 (Odonata: Coenagrionidae) - Vilela, Diogo Silva; Anjos-Santos, Danielle; Koroiva, Ricardo; Cordero-Rivera, Adolfo; Guillermo-Ferreira, Rhainer (Zootaxa, 2020)
Endemic to Brazil, the genus Minagrion Santos, 1965 is revised for the first time. The genus contains five species, and here we establish diagnostic characters, keys and drawings for both sexes. Furthermore, we propose the synonymy of M. franciscoi Machado & Bedê, 2015 new syn. with M. caldense Santos, 1965.